Parents' legal obligation towards their children under islamic law / Norhanisah Johar, Redzy Rezali and Norhazwan Hassan - Johar, Norhanisah; Rezali, Redzy; Hassan, Norhazwan (2007)
This study is on Islamic Family Law regarding the obligations and responsibilities of the parents to provide proper maintenance to their children. This study focused on the children's rights that consist in the legal obligation of their parents towards them under Islamic perspective. This study has been conducted in accordance to the aspect of seriousness of the violation of the children's right. This study will explore on the types of parents5 obligations and determine which is 'wajib' and sunnah\ Other than that this study also will look at the various status of the child and the effect of their status to their right The statuses are legitimate child, illegitimate child and adopted child. We also take into consideration the problem and situation of converted parents and its effect to their children's right This paper will study on the factors that bring to the violation of children's right and also the consequences that will be appear because of the violation. This research will analyze the authority in Al Quran and Al-Hadith to support the argument pertaining the violation of children's right which is getting serious nowadays.